Binder-free mechanochemical metal–organic framework nanocrystal coatings. Issue 6 (28th January 2022) - Lin, Rijia; Yao, Yuqi; Zulkifli, Muhammad Yazid Bin; Li, Xuemei; Gao, Shuai; Huang, Wengang; Smart, Simon; Lyu, Miaoqiang; Wang, Lianzhou; Chen, Vicki; Hou, Jingwei
Abstract : A quick, verstile and binder-free technique to generate MOF coatings on various substrates. Abstract : The practical applications of metal–organic frameworks (MOFs) usually require their assembly into mechanically robust structures, usually achieved via coating onto various types of substrates. This paper describes a simple, scalable, and versatile mechanochemical technique for producing MOF nanocrystal coatings on various non-prefunctionalised substrates, including ZrO2, carbon cloth, porous polymer, nickel foam, titanium foil and fluorine-doped tin oxide glass. We revealed the detailed mechanisms that ensure the coating's stability, and identified the coating can facilitate the interfacial energy transfer, which allowed the electrocatalysis application of the MOF coating on conductive substrates. We further demonstrated that coatings can be directly generated in a one-pot fashion by ball milling MOF precursors with substrates.